Historical blocking: IR 2022-08-12 to 2022-08-23 (Iran) - Voidly (2022)
CRITICAL severity censorship detected in Iran. Confidence: 99%. Data sourced from ooni-historical-backfill.
Censorship Incident ID: IR-2022-0510
Keywords: censorship; IR; censorship; critical